Regional drug information center disseminates educational materials related to the COVID-19 pandemic - Jaqueline Rocha Borges dos Santos (Elsevier, 2021)
Background: Drug information centers (DIC) play an important role in providing correct and scientifically supported information on medicinal products. In the pandemic scenario, this action is considered fundamental to the process of health education. Objective: To describe and identify the dissemination of educational materials and their acceptance regarding the COVID-19 pandemic by a regional drug information center (RDIC) linked to a Brazilian public university. Method: The educational materials were disseminated in the communication channels (social media) of the RDIC and university. Seventeen educational notices were produced and disclosed from May to August 2020. The measure of reach was considered to be the number of “likes”, sharing and number of people reached. Results: Overall, 28.9% (n = 4071) of the online visitors “liked” the material about vaccines tested for COVID-19, followed by 12.9% (n = 1824) “likes” of the material about ivermectin for COVID-19 treatment, and 8.9% (n = 1250) “likes” of the material that explained the time necessary to develop and test a vaccine and the duration of the pandemic. Conclusion: The interest expressed by the “likes” of educational materials about vaccines indicates that the DIC in question has a strategic role in disseminating scientifically backed information about the COVID-19 pandemic.